2019
DOI: 10.1186/s40792-019-0607-8
|View full text |Cite
|
Sign up to set email alerts
|

Pure laparoscopic liver resection for giant liver hemangioma with extrahepatic growth based on preoperative 3-dimensional simulation: A case report

Abstract: Background Performing laparoscopic liver resection for giant hemangiomas is challenging, and careful preoperative planning is essential. Controlling intraoperative bleeding and handling surgical instruments within a limited workspace is necessary. Case presentation In the present case, the patient was a 38-year-old woman diagnosed with a 16-cm giant liver hemangioma in segment 5/6, with extrahepatic growth. Preoperative three-dimensional simulations for port placement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Pre-operative TAE prior to LLR of GHs has only been described in a few case reports [ 7 , 8 , 9 ]. However, given the anecdotal nature of these studies, no consistent information is provided regarding the embolizing materials, limiting the reproducibility of these data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-operative TAE prior to LLR of GHs has only been described in a few case reports [ 7 , 8 , 9 ]. However, given the anecdotal nature of these studies, no consistent information is provided regarding the embolizing materials, limiting the reproducibility of these data.…”
Section: Discussionmentioning
confidence: 99%
“…Some case series of successful laparoscopic liver resections (LLRs) for selected hepatic hemangiomas are currently available in the literature [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ] yet all authors highlight several technical difficulties; high rates of conversion to open surgery and massive intraoperative blood loss are the most challenging. In addition, there is growing evidence that size itself is among the most important risk factors associated with uncontrollable bleeding and limited intrabdominal surgical workspace [ 2 , 13 , 14 ], making LLR a particularly challenging choice for the treatment of GHs exceeding 10 cm.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of surgical robot has overcome many of the shortcomings of traditional laparoscopic surgery [15] by providing high definition three-dimensional visualization, EndoWrist instruments with 7 degrees of freedom of motion, and tremor filtration. Cohort studies on robot-assisted and/or laparoscopic liver resection for hemangioma have been reported, but most of these studies are small case series or case reports [16][17][18][19][20]. To our knowledge, there have been no studies directly comparing robot-assisted liver resection (RALR) versus laparoscopic liver resection (LLR) for liver hemangiomas.…”
mentioning
confidence: 99%